Scandinavia: A Bibliographic Survey of Literature. - DEPARTMENT OF THE ARMY WASHINGTON D C (1975)
This unclassified bibliographic survey was prepared to fill the need for information on Scandinavia, a strategically important area of Europe, about which, generally speaking, there is considerable lack of current literature in the English language, suitable for inclusion in DA pamphlets. The materials delve into the military, political, economic, and sociological aspects from both friendly and unfriendly sources. No effort has been made to delete or exclude references by reason of their controversial nature. Library of Congress Catalog Card No. 74-14935.